Hopelessness in palliative care for people with motor neurone disease: Conceptual considerations. (February 2020) - Poppe, Christopher
The concepts of hope and its absence, hopelessness, are seen as crucial in palliative care for people with motor neurone disease. A primary measure in psychological research on hopelessness in people with motor neurone disease is the Beck Hopelessness Scale. This scale can be understood as being conceptually based on the philosophical standard account of hope, which understands hope as an intentional expectancy. This essay argues that this is a misconstruction of hopelessness in palliative care. Rather, pre-intentional hope is essential for palliative care of people with motor neurone disease. Pre-intentional hope enables the formation of intentional hopes and is intrinsically relational. Finally, it is argued that the absence of pre-intentional hope should not be subjected to psychiatric diagnosis, for example, in the form of demoralization disorder.